The Human Microbiome and its Role in Understanding the COVID-19 Pandemic - Bohdan W. Wasilewski (Medical Science: Trends and Innovations Vol. 3, 2025)
This publication is addressed mainly to that narrow group of experts who are prepared to commit to analysing facts that involve the competencies of other scientific disciplines. This group, unlike the general public, which has exhausted its capacity to accept new, difficult or threatening facts of the pandemic, is willing to undertake that challenge. A significant obstacle to a broader scientific discussion is the hermetic vocabulary and separated definitions of concepts used in specific biological disciplines. Another is the need to absorb a large amount of new, not fully ranked information, related to the explosion of knowledge in different fields. A further barrier is related to overcoming the mental barriers, which were written in previous articles. These are concerned with how information related to the COVID-19 pandemic was received and interpreted. This narrow focus–restricted perception, reflects lived experience in dealing with viral infections in everyday life, and it mirrors social relationships in that the virus must be fought, eliminated or neutralized by humans. However sceptical the reception of the following concept may be received, it is perhaps necessary to counterintuitively identify with the virus; after all, the body is a community in which viruses dominate quantitatively in relation to body cells, as do the prions and bacteria cohabiting within it. In addition to the longitudinal perception of evolution, analysing the formation of species over time, there is an equally important vertical dimension. This consists of the functional integration of different species of living beings (including viruses) in which the human organism is a multi-level product of the vertical course of evolution. The author’s hypothesis suggests that the essence of the COVID-19 pandemic is the reduced effectiveness of evolutionarily born mechanisms, with which humans are equipped. These enable humans to coexist with viruses, both in their endogenous form (constitutive of our bodies) and exogenous with which humans continuously interact including those which are pathogenic. This publication seeks to present the complexity and interdependence of the cellular and subcellular organisms that compose the human body, and their sensitivity to toxic influences associated with human industrial activities.